2023
DOI: 10.1029/2022jd038228
|View full text |Cite
|
Sign up to set email alerts
|

Data‐ and Model‐Based Urban O3 Responses to NOx Changes in China and the United States

Xiaokang Chen,
Min Wang,
Tai‐Long He
et al.

Abstract: Urban air pollution continues to pose a significant health threat, despite regulations to control emissions. Here we present a comparative analysis of urban ozone (O3) responses to nitrogen oxide (NOx) changes in China and the United States (US) over 2015–2020 by integrating various data‐ and model‐based methods. The data‐based deep learning (DL) model exhibited good performance in simulating urban air quality: the correlation coefficients (R) of O3 daily variabilities with respect to independent O3 observatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 42 publications
0
2
0
Order By: Relevance
“…In this study, we explore the capability of DL to make O 3 predictions across different spatial and temporal domains using a model with integrated CNNs and LSTM neural networks. The architecture of this DL model has been applied in recent studies to investigate the changes in CO, nitrogen oxide (NO x ) and O 3 (Chen et al., 2023; Han et al., 2022; He et al., 2022a). The DL model was trained and validated with surface O 3 observations in China and the US in 2015–2018.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, we explore the capability of DL to make O 3 predictions across different spatial and temporal domains using a model with integrated CNNs and LSTM neural networks. The architecture of this DL model has been applied in recent studies to investigate the changes in CO, nitrogen oxide (NO x ) and O 3 (Chen et al., 2023; Han et al., 2022; He et al., 2022a). The DL model was trained and validated with surface O 3 observations in China and the US in 2015–2018.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies demonstrated applications of data‐driven techniques to provide air quality forecasts (Bi et al., 2022; Zhang et al., 2023), spatial extensions of atmospheric observations (Liu et al., 2022; Wei et al., 2023), more accurate or rapid CTM simulations (Shen et al., 2022; Xing et al., 2020), and atmospheric pollutant emission estimates (He et al., 2022b; Xing et al., 2022). Furthermore, recent studies have highlighted the importance of data‐driven techniques to provide a better understanding of atmospheric ozone (O 3 ), for example, the contributions of meteorological and anthropogenic sources to observed O 3 changes (Chen et al., 2023; Wang et al., 2023; Weng et al., 2022).…”
Section: Introductionmentioning
confidence: 99%